2018
DOI: 10.1088/1748-0221/13/05/c05010
|View full text |Cite
|
Sign up to set email alerts
|

Chemical induced demineralization study in cortical bone

Abstract: In this work we present a study of demineralization in bovine cortical bone. We selected 9 fresh cortical bone samples from 2 diaphyseal femurs for analysis. Samples were demineralized for 24 h, 48 h, 72 h and 96 h using two concentrations of EDTA with different pH: EDTA 0.1 M (pH 10, alkaline) and EDTA 0.5 M (pH 7.4, neutral). We have employed µ-X-ray fluorescence (µ-XRF) and X-ray diffraction (XRD) to assess the degree of demineralization. EDTA solutions were analyzed for Calcium (Ca) and Phosphorous (P) ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…This process is based on the use of EDTA to chelate some mineral composition in specimens (Balayan et al 2015). The concentration and pH of EDTA were previously reported to affect the demineralization process of the teeth or on the bovine cortical bone (Sales et al 2018). Hasap et al (2020) found that total demineralization combined with DNA purification by commercial kit improved DNA yield and STR profiles (Hasap et al 2020).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This process is based on the use of EDTA to chelate some mineral composition in specimens (Balayan et al 2015). The concentration and pH of EDTA were previously reported to affect the demineralization process of the teeth or on the bovine cortical bone (Sales et al 2018). Hasap et al (2020) found that total demineralization combined with DNA purification by commercial kit improved DNA yield and STR profiles (Hasap et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…To determine the calcium level chelated from the bone in demineralization buffer after the completed demineralization process, the calcium concentration was quantified by atomic absorption spectrophotometry (Sales et al 2018). The amount of calcium in the EDTA solution was calculated comparing the calcium standard curve and expressed as mg/dL.…”
Section: Determination Of Calcium In Demineralization Buffermentioning
confidence: 99%
See 3 more Smart Citations